RELATIONSHIP OF EXCLUSIVE BREASTFEEDING WITH UTERINE INVOLUTION POSTPARTUM AT PMB NISBAHNINGSIH - Fitriani, Yunita; Farihatin, Yuyun; Rukanah, Rukanah (Universitas Airlangga, 2023)
Introduction: Process Breastfeeding affects the decrease in fundal height. that mother having impaired lactation will hinder the process of uterine involution which will result in bleeding. one way to prevent bleeding during puerperium is to give ASI as early as possible maybe the baby. Methods: This study uses an analytical method with a cross sectional approach. The sampling technique was non probability with accidental sampling method, where the researcher collected samples until fulfilled at PMB Nisbahningsih Gresik as many as 21 postpartum mothers. Results: The test results as many as 21 post partum mothers with statistical analysis used contingency coefficient test showed a p = 0.005 < α = 0.05, there was a significant the relationship of exclusive breastfeeding with uterine involution process in postpartum mothers at PMB Nisbahningsih gresik. Conclusions: The results of this study it can be concluded thah that there is a relationship between exclusive breastfeeding on uterine involution. Therefore it is expected that post partum mothers give exclusive breastfeeding to their babies so that the process of runs normally.